Established PABPN1 intranuclear inclusions in OPMD muscle can be efficiently reversed by AAV-mediated knockdown and replacement of mutant expanded PABPN1. (2nd July 2019) - Malerba, Alberto; Klein, Pierre; Lu-Nguyen, Ngoc; Cappellari, Ornella; Strings-Ufombah, Vanessa; Harbaran, Sonal; Roelvink, Peter; Suhy, David; Trollet, Capucine; Dickson, George
Abstract: Oculopharyngeal muscular dystrophy (OPMD) is a rare autosomal dominant late-onset muscular dystrophy affecting approximately 1:100 000 individuals in Europe. OPMD is mainly characterized by progressive eyelid drooping (ptosis) and dysphagia although muscles of the limbs can also be affected late in life. This muscle disease is due to a trinucleotide repeat expansion in the polyA-binding protein nuclear-1 gene. Patients express a protein with an 11–18 alanine tract that is misfolded and prone to form intranuclear inclusions, which are the hallmark of the disease. Other features of OPMD include muscle fibrosis and atrophy in affected muscles. Currently, no pharmacological treatments are available, and OPMD patients can only be referred to surgeons for cricopharyngeal myotomy or corrective surgery of extraocular muscles to ease ptosis. We recently tested a two-AAV `silence' and `replace' vector-based gene therapy treatment in a mouse model of OPMD. We demonstrate here that this gene therapy approach can revert already established insoluble aggregates and partially rescues the muscle from atrophy, which are both crucially important since in most cases OPMD patients already have an established disease when diagnosed. This strategy also prevents the formation of muscle fibrosis and stabilizes the muscle strength to the level of healthy muscles. Furthermore, we show here that similar results can be obtained using a single AAV vector incorporating both the `silence' and `replace' cassettes. These results further support the application of a gene therapy approach as a novel treatment for OPMD in humans.